Carbon Nanotube Synthesis via the Calciothermic Reduction of Carbon Dioxide with Iron Additives. (15th July 2015) - Kikuchi, Tatsuya; Ishida, Ryoma; Natsui, Shungo; Kumagai, Takehiko; Ogino, Isao; Sakaguchi, Norihito; Ueda, Mikito; Suzuki, Ryosuke O.
Abstract : The novel fabrication of multi-walled carbon nanotube (MWCNT)/cementite (Fe3 C) nanocomposites was demonstrated via the calciothermic reduction of carbon dioxide (CO2 ) through electrolysis in molten CaCl2 /CaO with iron additives at 1173 K. In this technique, CO2 generated from a graphite anode is reduced to carbon with a metallic calcium reductant formed on a graphite cathode via electrolysis in molten salt. Calciothermic reduction without iron additives resulted in the formation of onion-like carbons (OLCs) with spherical graphite layers and thin graphite sheets. In contrast, MWCNT/Fe3 C nanocomposites and OLCs were successfully fabricated via calciothermic reduction with iron additives through their catalytic activities.